The structure of the Shiga toxin 2a A‐subunit dictates the interactions of the toxin with blood components. (18th January 2019) - Brigotti, Maurizio; Orth‐Höller, Dorothea; Carnicelli, Domenica; Porcellini, Elisa; Galassi, Elisabetta; Tazzari, Pier Luigi; Ricci, Francesca; Manoli, Francesco; Manet, Ilse; Talasz, Heribert; Lindner, Herbert H.; Speth, Cornelia; et al.
Abstract: Hemolytic uremic syndrome (eHUS) is a severe complication of human infections with Shiga toxins (Stxs)‐producing Escherichia coli . A key step in the pathogenesis of eHUS is the interaction of Stxs with blood components before the targeting of renal endothelial cells. Here, we show that a single proteolytic cleavage in the Stx2a A‐subunit, resulting into two fragments (A1 and A2) linked by a disulfide bridge (cleaved Stx2a), dictates different binding abilities. Uncleaved Stx2a was confirmed to bind to human neutrophils and to trigger leukocyte/platelet aggregate formation, whereas cleaved Stx2a was ineffective. Conversely, binding of complement factor H was confirmed for cleaved Stx2a and not for uncleaved Stx2a. It is worth noting that uncleaved and cleaved Stx2a showed no differences in cytotoxicity for Vero cells or Raji cells, structural conformation, and contaminating endotoxin. These results have been obtained by comparing two Stx2a batches, purified in different laboratories by using different protocols, termed Stx2a(cl; cleaved toxin, Innsbruck) and Stx2a(uncl; uncleaved toxin, Bologna). Stx2a(uncl) behaved as Stx2a(cl) after mild trypsin treatment. In this light, previous controversial results obtained with purified Stx2a has to be critically re‐evaluated; furthermore, characterisation of the structure of circulating Stx2a is mandatory to understand eHUS‐pathogenesis and to develop therapeutic approaches.